Tubuh Perempuan dan Kekerasan Seksual: Pandangan Filosofis-Teologis tentang Tubuh dan Studi Dokumentasi terhadap DKG-PGI - Tonta, Rex Firenze (Institut Agama Kristen Negeri Toraja, 2023)
This research focuses on and aims to recover the view of objectivating the female body, which is reduced to merely satisfying male lust, a source of sin, and other negative attachments. This perspective is suspected to be one of the factors in the sexual violence that occurs. The research method used in this research is qualitative, with a philosophical-theological approach. The philosophical approach uses Armada Riyanto's thoughts on “Menjadi-Mencintai” and “Relasionalitas:, while theologically using the human concept in the Document on Church Unity (DKG), Joas Adiprasetya's thoughts on the body in “the Labirin Kehidupan”, and the Theology of the Body of Pope John Paul II's. Beside that, this research also uses a documentation study approach to the DKG-PGI as well as several points of discussion in the PGI MPL annual meeting related to the spirituality of modesty. The findings of this research, that women's bodies are also in the image and likeness of God, and women's bodies should be respected by not crossing the boundaries of access so that sexual violence occurs. Beside that, in the findings from the documentation study on DKG, there is not a single word explicitly about sexual violence, although perhaps PGI discusses it in a larger scope, namely human rights. In this research, a possible offer to respond to the complexity of problems related to sexual violence within the scope of churches in Indonesia is to include in the DKG-PGI the church's commitment to jointly address and prevent sexual violence; encourage member churches to prepare prospective ministers and ministers with an awareness of the knowledge of sexual violence, such as by developing a 'Theology of the Body' and practicing a spirituality of moderation; on the other hand, if sexual violence has occurred, it is important to provide a safe place and advocate for victims of sexual violence.